1985
DOI: 10.3109/00498258509045354
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative metabolism of carbazeranin vitroby liver cytosol of baboon and man

Abstract: The metabolism of carbazeran has been investigated in vitro using liver cytosol from dog, baboon and man. Carbazeran was not metabolized in cytosol prepared from dog liver but was rapidly metabolized to a single product in baboon- and human-liver cytosol. The product was identified as 4-hydroxy carbazeran. The enzyme responsible for the 4-hydroxylation of carbazeran in vitro was shown by the use of inhibitors to be liver aldehyde oxidase. Species differences in the metabolism of carbazeran in vitro correlate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 10 publications
1
42
1
Order By: Relevance
“…3). Together with reaction specificities of carbazeran 4-hydroxylation (Kaye et al, 1985) and zoniporide 2-hydroxylation , potent inhibition by hydralazine offers additional evidence for cutaneous activity of AO.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3). Together with reaction specificities of carbazeran 4-hydroxylation (Kaye et al, 1985) and zoniporide 2-hydroxylation , potent inhibition by hydralazine offers additional evidence for cutaneous activity of AO.…”
Section: Discussionmentioning
confidence: 99%
“…Although AO has long been known to oxidize nitrogen-containing heterocycles (Knox, 1946;Stanulovi c and Chaykin, 1971;Stubley et al, 1979), its importance to drug metabolism first emerged in the case of carbazeran, a phosphodiesterase-2 inhibitor discontinued due to low oral bioavailability and short half-life in humans (Kaye et al, 1984(Kaye et al, , 1985. Based on analysis of chemical structure, a recent review suggested that a large number of drugs on the market (;13%) or candidate drugs (almost 45% of drugs in development) could be AO substrates (Pryde et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations